Predictive modeling and validation of arsenite removal by a one pot synthesized bioceramic buttressed manganese doped iron oxide nanoplatform. Issue 52 (27th June 2017) - Dhiman, Nitesh; Markandeya,; Fatima, Faimy; Saxsena, Prem N.; Roy, Somendu; Rout, Prashant K.; Patnaik, Satyakam
Abstract : Arsenite removal by a one pot synthesized bioceramic buttressed manganese doped iron oxide nanoplatform. Abstract : In the present study, a series of bioceramic capped manganese doped superparamagnetic iron oxide (SPIONs) nanoparticles (mHAP NPs) were synthesized by one pot in situ reduction. The aging of the bioceramic on the SPIONs was optimized to achieve variation in functionality, morphology, magnetic susceptibility, shape and size of the NPs and ultimately remediation effectiveness of arsenite; As(iii ). Results indicate that among various synthesized NPs, the 6 h aged mHAP NPs with 27 emu magnetic susceptibility, 57.30 m 2 g −1 surface area and 75.64 Å average pore diameter offer the best option as an adsorbent for posthaste removal of As(iii ) from synthetically spiked water. Further, predictive modeling using response surface based Central Composite Design (CCD) was applied to achieve and optimize process parameters for the removal of As(iii ) by mHAP NPs keeping variable operational parameters to a minimum in batch experiments. The individual and collective effect of four process parameters, i.e. pH, mHAP NP dose, contact time and initial As(iii ) concentration on As(iii ) adsorption were studied. The results from statistical design signify that, with 0.2 g L −1 of above mHAP NPs adsorbent dose, 98% As(iii ) (initial concentration 0.1–0.4 mg L −1 ) removal was possible in 210 min at pH 6.5 which is well within the prescribed value as per WHO guidelines. The adsorption process of As(iii ) onto mHAP NPs showed excellent correlation with a Langmuir isotherm with a maximum adsorption capacity of 12.0 mg g −1 . Kinetic and thermodynamic studies reveal pseudo-second-order kinetics with an exothermic and spontaneous adsorption of As(iii ) on the synthesized adsorbent. Cyclic regeneration of mHAP NPs indicated positive impact in remediation technology at low production cost.